2007
DOI: 10.1073/pnas.0611434104
|View full text |Cite
|
Sign up to set email alerts
|

An obligatory requirement for the heterotrimeric G protein G i3 in the antiautophagic action of insulin in the liver

Abstract: Heterotrimeric G proteins of the Gi class have been implicated in signaling pathways regulating growth and metabolism under physiological and pathophysiological conditions. Knockout mice carrying inactivating mutations in both of the widely expressed G␣ i class genes, G␣i2 and G␣i3, demonstrate shared as well as genespecific functions. The presence of a single active allele of G␣i3 is sufficient for embryonic development, whereas at least one allele of G␣ i2 is required for extrauterine life. Mice lacking both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
138
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(152 citation statements)
references
References 39 publications
14
138
0
Order By: Relevance
“…These findings serve as an important basis for the identification of the underlying mechanisms of redundancy versus isoform specificity of Ga i2 and Ga i3 . Such mechanisms could be based on a different subcellular localization of these isoforms (16,47), structural differences in regions different from the receptor-or effector-binding domains, as well as the total amount of Ga i proteins in the cells, with the latter obviously not playing a decisive role in our model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings serve as an important basis for the identification of the underlying mechanisms of redundancy versus isoform specificity of Ga i2 and Ga i3 . Such mechanisms could be based on a different subcellular localization of these isoforms (16,47), structural differences in regions different from the receptor-or effector-binding domains, as well as the total amount of Ga i proteins in the cells, with the latter obviously not playing a decisive role in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, like most other cell types (16), express Ga i2 in much higher concentrations than Ga i3 (23). Importantly, however, low Ga i3 can compensate for the lack of high Ga i2 in LPS-induced macrophage activation and C5aR-regulated erythrophagocytosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS16 RNA levels were also significantly elevated in the liver of ATdeficient patients when compared with liver from normal and disease controls. Although we did not originally understand the functional importance of these specific changes in gene expression, a recent study by Gohla et al 35 has led to the hypothesis that upregulation of RGS16 plays a role in Figure 3 A hypothetical model for the role of RGS16 in activating hepatic autophagy in AT deficiency. The intermediates of the insulin-signaling pathway (Akt, TSC1 and 2, Rheb and mTOR) are shown downstream of the insulin receptor as well as the effect of amino acids.…”
Section: Potential Mechanisms For Activation Of Hepatic Autophagy In mentioning
confidence: 99%
“…Recently it has been found that both insulin and amino acids, such as phenylalanine, could also work through a pathway related to G␣i3 because deletion of G␣i3 eliminates their protective effects against protein degradation in perfused liver. 38 G␣i3 is a G␣ subunit of heterotrimeric G proteins, and its positive role (in guanosine diphosphate [GDP]-binding status) in autophagy induction was shown previously in a colon cancer cell line. 39 Consistently, an early study implicated the involvement of guanosine triphosphatase (GTPase) activity in autophagy induction in permeabilized hepatocytes.…”
Section: Role Of Autophagy In Nutrient and Energy Metabolism In Hepatmentioning
confidence: 99%